Nonfouling poly(ethylene oxide) layers end-tethered to polydopamine - Pop-Georgievski, Ognen; Verreault, Dominique; Kölsch, Patrick (Langmuir, 2012)
Nonfouling surfaces capable of reducing protein adsorption are highly desirable in a wide range of applications. Coating of surfaces with poly(ethylene oxide) (PEO), a water-soluble, nontoxic, and nonimmunogenic polymer, is most frequently used to reduce nonspecific protein adsorption. Here we show how to prepare dense PEO brushes on virtually any substrate by tethering PEO to polydopamine (PDA)-modified surfaces. The chain lengths of hetero-bifunctional PEOs were varied in the range of 45-500 oxyethylene units (Mn = 2000-20 000). End-tethering of PEO chains was performed through amine and thiol headgroups from reactive polymer melts to minimize excluded volume effects. Surface plasmon resonance (SPR) was applied to investigate the adsorption of model protein solutions and complex biologic medium (human blood plasma) to the densely packed PEO brushes. The level of protein adsorption of human serum albumin and fibrinogen solutions was below the detection limit of the SPR measurements for all PEO chains end-tethered to PDA, thus exceeding the protein resistance of PEO layers tethered directly on gold. It was found that the surface resistance to adsorption of lysozyme and human blood plasma increased with increasing length and brush character of the PEO chains end-tethered to PDA with a similar or better resistance in comparison to PEO layers on gold. Furthermore, the chain density, thickness, swelling, and conformation of PEO layers were determined using spectroscopic ellipsometry (SE), dynamic water contact angle (DCA) measurements, infrared reflection-absorption spectroscopy (IRRAS), and vibrational sum-frequency-generation (VSFG) spectroscopy, the latter in air and water.
Gesehen am 28.11.2018